2011
DOI: 10.1002/minf.201000162
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Conformational Flexibility of Serine Racemase by Combining Targeted Molecular Dynamics, Conformational Sampling and Docking Studies

Abstract: Serine racemase (SR) is a PLP-dependent enzyme catalyzing the racemization of L-Ser into D-Ser, which is now recognized as an endogenous co-agonist at the NMDA receptor complex. As indicated by available X-ray structures, SR undergoes significant conformational changes during ligand recognition, and it is conceivable that, in addition to the reported X-ray structures, other intermediate conformational states may have relevance in drug discovery studies. Targeted molecular dynamics (TMD) simulations are an effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Despite the range of activity allowed only a rough SAR, these results somehow confirmed the presence of a lipophilic pocket in the proximity of the enzyme active site where the pyrazole substituent can locate, as previously noticed by us 27 , 36 , 37 . In addition, the activity shown by compounds 4e and 5f demonstrated that the size of the molecule may have some influence on the binding to the enzyme pocket.…”
Section: Resultssupporting
confidence: 84%
“…Despite the range of activity allowed only a rough SAR, these results somehow confirmed the presence of a lipophilic pocket in the proximity of the enzyme active site where the pyrazole substituent can locate, as previously noticed by us 27 , 36 , 37 . In addition, the activity shown by compounds 4e and 5f demonstrated that the size of the molecule may have some influence on the binding to the enzyme pocket.…”
Section: Resultssupporting
confidence: 84%
“…In fact, if a virtual screening is carried using the open conformation, less specific compounds might be identified, whereas if the screening is carried out using the closed conformation, the reduced space may lead to the identification of ligands with reduced size and affinity. In an effort to overcome these limitations and to include SerR conformational flexibility in virtual screening investigations, targeted molecular dynamics of SerR was combined with conformational sampling and docking studies . Results suggest that a virtual screenings of SerR carried out sampling a defined number of protein conformations along the open-to-closed state pathway might lead to the identification of selective and high affinity enzyme inhibibitors.…”
Section: Amino Acid Racemases As Drug Targetsmentioning
confidence: 99%
“…Nevertheless, it can be expected that the individual enzyme conformations captured by X‐ray crystallography are not sufficient to display all the features needed for a proper interaction with the substrate or with the inhibitors. In this context, MD simulations have already proven to be useful tools to catch the structural details of the inhibition mechanism for compounds targeting β‐family PLP‐dependent enzymes 20…”
Section: Introductionmentioning
confidence: 99%